Development and Validation of the Five-Factor Borderline Inventory–Super Short Form and Screener - DeShong, Hilary L.; Mason, Courtney K.; Porter, Ben; Kelley, Kren; Mullins-Sweatt, Stephanie N.; Lynam, Donald R.; Miller, Joshua D.; Widiger, Thomas (Assessment (Odessa, Fla.), 2025)
The Five-Factor Borderline Inventory (FFBI) and FFBI-Short Form (FFBI-SF) are 120-item and 48-item measures that assess the underlying maladaptive personality traits of borderline personality disorder (BPD). The purpose of this study was to develop a super short form (FFBI-SSF) and an FFBI-Screener to facilitate the use of dimensional trait measures for BPD. Using item response theory analyses, the 48-item measure was reduced to 22 items using a large undergraduate sample (N = 1300) and then retested using a Mechanical Turk sample (N = 602), demonstrating strong replicability. IRT was again used to further reduce the measure from 22 items to four items to provide a brief screening tool. Correlations of the FFBI-SSF and Screener with measures of BPD-related variables were compared across five samples (N = 919, 204, 580, 281, and 488). Overall, the FFBI-SSF showed similar relations to the FFBI-SF at the full scale and domain-level scales, while the FFBI-screener demonstrated similar relations at the full scale level. This super short form and screener may best be used in large-scale research studies or as part of a screening tool in clinical settings.